A carbohydrate polymer is a critical variable in the formulation of drug nanocrystals: a case study of idebenone. (2nd December 2019) - Ma, Minchao; Zhang, Guangshuai; Li, Wen; Li, Mo; Fu, Qiang; He, Zhonggui
ABSTRACT: Objective : Stabilizers, especially carbohydrate polymers, have been shown to be necessary for the stabilization of drug nanocrystals. However, the impacts of select stabilizers on the in vitro and in vivo efficacy of therapeutics have rarely been reported. The aim of this study was to evaluate the importance of stabilizers in the formulation of drug nanocrystals. Research design and methods : Idebenone nanocrystals (IDBNC) stabilized by various stabilizers were formulated using a milling method. The in vitro dissolution profiles in water and in situ absoprtion were compared. Finally, an in vivo pharmacokinetic study was performed. Results : The IDBNC profiles were found to have acceptable sizes and similar morphology and crystallinity. The dissolution profiles of IDBNC stabilized by different stabilizers were notably different, indicating the critical influence of stabilizers on the release rate of IDB. The Soluplus-stabilized IDBNC (IDBNC400 nm /Soluplus) achieved better absorption than HPMC stabilized IDBNC (IDBNC400 nm /HPMC). The pharmacokinetic study demonstrated that Soluplus-stabilized IDBNC had preferable kinetics, with an AUC0–24h of IDBNC400 nm /Soluplus (3.08-fold relative to IDB suspension), compared to IDBNC400 nm /HPMC (1.88-fold). Conclusions : Choice of stabilizer plays an important role in the formulation of IDBNC. We anticipate that the role of stabilizers in the pharmacokinetic disposition of IDBNC has significant implications for a wide range of other drug crystal formulations.